Analysis of Items for Selection of High School Biology Olympics Participants - Ahmad Subari; Zulyusri Zulyusri; Violita Violita; Restu Fitriani (Magister Pendidikan Biologi, Universitas Negeri Medan, 2021)
Based on observations at school, the teacher has not analyzed the items for the biology Olympics selection that will be tested on the participants. This study aims to determine the quality of the questions of the MAN Model Biology Olympics in Jambi City. This research is a quantitative descriptive study with the subject of class X students participating in the biology Olympics training. Data were obtained through test instruments in the form of multiple choice questions, answer sheets, and answer keys. The data analysis technique used Anates 4.0.9 program. The results showed the level of validity at the coefficient level of 5%, namely, valid questions amounted to 13 questions and 27 questions invalid. At the level of reliability obtained a value of 0.46 with a sufficient category. At the level of difficulty, there are 3 questions that are categorized as easy, 16 are categorized as medium, and 21 are categorized as difficult. Then on the discriminatory power there are 7 questions categorized as very good, 12 categorized as good, 7 categorized as bad and 14 categorized as very bad. Furthermore, in the distractor quality analysis, there are 4 questions with very good and good distractor quality, while the rest have distractor qualities in the criteria of poor, bad, and very bad. Based on the results of the item analysis recap, there is 1 question that can be used directly, 12 questions can be used but need to be improved and 27 questions cannot be used.